Prognostic significance of clinical presentation, induction and rescue treatment in 42 cases of canine centroblastic diffuse large B‐cell multicentric lymphoma in the United Kingdom. (22nd December 2017) - Davies, O.; Szladovits, B.; Polton, G.; Garden, O. A.; Leo, C.; Lara‐Garcia, A.
Abstract : Canine lymphoma is a heterogeneous group of diseases and many previous studies have evaluated the response of a mixed population of lymphoma cases to one specific treatment protocol. The aim of this retrospective study was to describe the outcome and prognostic factors in 42 cases of multicentric centroblastic diffuse large B‐cell lymphoma treated with either a COP‐type (35%) or CHOP‐type (64%) induction chemotherapy. The objective response rate to induction therapy was 94%; entire dogs had a greater rate of complete vs partial remissions than neutered dogs ( P = .017). Median progression‐free survival for the first remission (PFS1) was 182 days; absence of anaemia at diagnosis ( P = .002) and pretreatment neutrophil:lymphocyte ratio (NLR) below 9.44 ( P = .015) were independently predictive of longer PFS1. Fifty‐eight percent of dogs received rescue protocols with an objective response rate of 81%; 31% of dogs received further rescue protocols (up to a total of 5) and the median number of protocols administered were 2. Median overall survival (OS) was 322 days, the 1‐year survival rate was 38% and the 2‐year survival rate was 9%. Lymphocyte:monocyte ratio above 1.43 ( P = .031), NLR below 11.44 ( P = .009), the combination of induction and rescue therapy ( P = .030) and the total number of doxorubicin doses used ( P = .002) were independently predictive of longer OS. Use of a COP‐type protocol induction compared with CHOP did not undermine OS providing doxorubicin was used as rescue therapy.